2013
DOI: 10.1155/2013/354582
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gene Expression Profiling in Human Cumulus Cells according to Ovarian Gonadotropin Treatments

Abstract: In in vitro fertilization cycles, both HP-hMG and rFSH gonadotropin treatments are widely used to control human follicle development. The objectives of this study are (i) to characterize and compare gene expression profiles in cumulus cells (CCs) of periovulatory follicles obtained from patients stimulated with HP-hMG or rFSH in a GnRH antagonist cycle and (ii) to examine their relationship with in vitro embryo development, using Human Genome U133 Plus 2.0 microarrays. Genes that were upregulated in HP-hMG-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
1
27
0
3
Order By: Relevance
“…it has also been shown that the expression of this gene is influenced by the presence of the estrogen receptor (71). other studies revealed that an increase in the expression DFNA5 may be affected by the hormonal stimulation of patients (72)(73)(74). assou et al (72) indicated that DFNA5 expression is increased in cumulus cells obtained from patients following rFSH stimulation, compared to cells obtained following hMG-HP stimulation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…it has also been shown that the expression of this gene is influenced by the presence of the estrogen receptor (71). other studies revealed that an increase in the expression DFNA5 may be affected by the hormonal stimulation of patients (72)(73)(74). assou et al (72) indicated that DFNA5 expression is increased in cumulus cells obtained from patients following rFSH stimulation, compared to cells obtained following hMG-HP stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…other studies revealed that an increase in the expression DFNA5 may be affected by the hormonal stimulation of patients (72)(73)(74). assou et al (72) indicated that DFNA5 expression is increased in cumulus cells obtained from patients following rFSH stimulation, compared to cells obtained following hMG-HP stimulation. These findings indicated that the high expression of DFNA5 detected in Gcs in this study may be the result of stimulation with rFSH.…”
Section: Discussionmentioning
confidence: 96%
“…Another factor with an inhibitory effect on the prostaglandin synthesis, ANXA1, was also upregulated both at the mRNA and the protein level in the pregnant uterus. Also GM2A mRNA and protein was more highly expressed during pregnancy and has been linked to embryo and blastocyst quality in human [48]. However, despite these biologically interesting molecules, overall overlap between differentially expressed genes in the pregnant vs. cyclic endometrium and differentially expressed proteins in the pregnant vs. cyclic UF was very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Наведені результати узгоджуються з даними, отриманими в інших дослідженнях [23]. Значна кореляція була виявлена між ембріональним розвитком на 3-тю добу та експресією ГРЕМ1 [24,25], а також, проте меншою мірою, між якістю ооцитів та ЦОГ2 і ГС2 [24]. Виявлений взаємозв'язок вмісту мРНК для цих генів і видом гонадотропіну, що використовувався для оваріальної сти-муляції [15,24,25].…”
Section: оглядиunclassified
“…Припускають, що селективне інгібування сигналізації сприяє лютеїнізації пристінкових ГК, підтримуючи при цьому кумулюсне розширення. Якщо це так, то безперервна експресія ГРЕМ1 в КК повинна представляти зрілий ооцит і прогнозує покращений розвиток ембріона [3,25]. Зниження ж експресії ГРЕМ1 може вказувати на пошкоджену ооцитарну функ-цію і кумулюсне розширення і, відповідно, свідчить про слабку репродуктивну здатність.…”
Section: оглядиunclassified